Pengaruh Vulva Hygiene Terhadap Penyembuhan Luka Perineum Pada Ibu Nifas Di Polindes Marengan Laok Kecamatan Kalianget - Adinda Ratih Tiara; Yulia Paramita Rusady (Universitas Islam Madura, 2022)
The process of childbirth often results in tearing of the birth canal which causes bleeding in varying amounts. One source of bleeding that comes from perineal wounds that require optimal care. Based on data obtained from the Polindes Marengan Laok, it showed that 7 postpartum mothers (70%) had their perineal wounds in 1 week still wet, moist, some even had pus. The purpose of this study was to determine the effect of vulvar hygiene on the healing of perineal wounds on the 7th day of postpartum women. This type of research is correlation analytic. Based on the time this research uses cross sectional. The independent variable is vulva hygiene and the dependent variable is perineal wound healing. The population is 30 postpartum mothers in Marengan Laok Village with a total sampling technique. Data collection techniques using questionnaires and checklists. Based on the cross tabulation, almost all respondents who performed vulvar hygiene well (88.2%) had their perineal wounds healed as many as 15 respondents, and respondents who lacked vulva hygiene mostly (62.5%) did not heal perineal wounds as many as 5 respondents. From the statistical test of the contingency coefficient using SPSS 18, it was found that 2 count > 2 table (7,297 > 5,991). Based on the coefficient value (0.442) there is a moderate relationship between vulva hygiene and healing of perineal of postpartum women in the Marengan Laok Village. Based on these conclusions, the solution that can be done is that health workers should further improve postnatal services, especially in conducting home visits to prevent, detect, and treat problems in the perineal wound healing process. Keywords: Vulva hygiene, perineal wound, postpartum mother.